3D art lab for kids : 32 hands-on adventures in sculpture and mixed media - including fun projects using clay, plaster, cardboard, paper, fiber beads and more! /: 32 hands-on adventures in sculpture and mixed media - including fun projects using clay, plaster, cardboard, paper, fiber beads and more!. (2013) - Schwake, Susan; Schwake, Rainer
No abstract available